Silencing MaxiK Activity in Corporal Smooth Muscle Cells Initiates Compensatory Mechanisms to Maintain Calcium Homeostasis - Calenda, Giulia (J Sex Med, 2011)
INTRODUCTION: The MaxiK potassium channel is regulated by voltage and intracellular calcium, and plays a critical role in regulating intracellular calcium concentration ([Ca(2+)](i)), which is the ultimate determinant of smooth muscle tone. Tight control of corpus cavernosum smooth muscle (CCSM) tone is critically important and misregulation can result in erectile dysfunction. AIM: Because of the tight functional linkage of MaxiK and calcium channel activity, the aim of this study was to determine the effects of silencing and pharmacological inhibition of MaxiK on calcium homeostasis and intercellular calcium signaling in CCSM cells. METHODS: We compared changes in the basal intracellular [Ca(2+)](i) and parameters defining intercellular calcium wave (ICW) spread in 48 hours MaxiK silenced CCSM cells vs. acute blockade of the channel with iberiotoxin. To analyze changes occurring in gene expression we performed micro-array analysis following MaxiK silencing for 48 hours. MAIN OUTCOME MEASURES: Changes in Fura-2 fluorescence intensities were measured to evaluate basal [Ca(2+)](i) levels and ICW parameters. Microarray analysis of global gene expression was performed. RESULTS: Forty-eight hours after MaxiK silencing the basal [Ca(2+)](i), the ICW amplitude and spread among CCSM cells were not markedly different in silenced compared to mock transfected controls, whereas short-term blockade significantly increased basal [Ca(2+)](i) level and amplified Ca(2+) signaling among CCSM cells. Micro-array analysis showed that several genes within Ca(2+) homeostasis and smooth muscle tone regulation pathways had significantly altered expression. CONCLUSIONS: Our results indicate that while short-term blockade of the MaxiK channel is associated with an increase in basal [Ca(2+)](i), Ca(2+) homeostasis is restored during the 48 hours period following silencing. We hypothesize that the different pathways regulating [Ca(2+)](i) and CCSM tone are linked through molecular crosstalk and that their coordinated regulation is part of a compensatory mechanism aimed to maintain Ca(2+) homeostasis and CCSM tone.